Studi Literatur Tanggapan Masyarakat terhadap Viralnya Fenomena Citayam Fashion Week di Tiktok - Widiya Okta Sapitri; Fardiah Oktariani Lubis; Flori Mardiani Lubis (Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
This paper aims to determine the public's response to the viral phenomenon of Citayam Fashion Week on Tiktok. This goal is motivated by the phenomenon of CFW becoming widespread and taking advantage of the Indonesian people. The type of research used is descriptive qualitative, then the data collection technique is in the form of a literature study that contains various kinds of references, both journal articles, articles, notes, and the results of previous research which data and information will be studied further. the results of the research contained in this study in the form of the Citayam Fashion Week phenomenon which is being discussed in the community has its own view. There are many people who see this phenomenon from what point of view. If we draw further from the existence of this phenomenon, its existence in Indonesia is very unique because it is still new and people need to adapt because of it. It can be seen from all aspects that it has its own positive and negative impacts. Back again to each individual who controls this CFW phenomenon. Keywords: Citayam Fashion Week, Phenomenon, Tiktok